Access To Medical Health Care And its Current Health Care Policy: Malaysia - Chong, Chyi Ming (2005)
The indications of Malaysia government to remove its subsidize policy in its health care system and privatizing certain hospitals and health care services has inflicted numerous heated debates and discussions among individuals and Non-Governmental Organizations (NGO). The author wishes to contribute some insightful information to the public through her research about Malaysia citizen’s access to medical health care inline with its current health care system and policy. Health care systems of Malaysia, United Kingdom and United States of America are being discussed separately and compare at wherever possible. Web survey questionnaires and hardcopies of questionnaires are sent out randomly to capture perception and preferences of users. The sample size for this study is 55. Collected data are run through a series of test for its significance and effect through a few models and they are Logit model, Probit model and Independent Sample T-test. Some variables were significant and some were not. But, rightfully, all variables tested should be significant and details are being discussed in findings. Current issues faced by the Malaysia health care system is further discuss. Limitations and future prospects are also put into discussion. Finally, ‘cause and effect’ is very fundamental to any implementation of new policy. Detailed planning and careful thought should be put in for any new policy implementation to avoid dissatisfaction and unwanted outcome.